Study on the demand for and supply of Evaluation Malawi - Dr. Hannock, Kumwenda (CLEAR-AA, 2013)
This report provides a review of two dimensions of evaluation practice in Malawi: (i) the conditions under which demand for evidence is generated; and (ii) the areas in which supply can be strengthened to meet and foster this demand. The review serves to highlight the prevalence of active, latent and potential demands for evaluation. The latent and potential demands are nested within requests for evidence from principals and government agents. This demand is not necessarily only conditioned by development partners, but results endogenously from government, based on articulated development objectives. Supply could in the short-term be strengthened through work with the main research centres of the Universities of Malawi (Centre for Social Research, Economics Department) and Lilongwe University of Agriculture and Natural Resources.
Keywords: Study on the demand for and supply of evaluation in Malawi